From Metabolite to Metabolome: Metabolomics Applications in Plasmodium Research - Yu, Xinyu; Feng, Gaoqian; Zhang, Qingfeng; Cao, Jun (Frontiers in Microbiology, 2021)
Research advances over the past few decades have greatly improved the metabolomics-based approaches in studying parasite biology and disease etiology which holds advantages in the investigation in varied metabolic requirement during life stages or followed transmission to their hosts, as well as fulfilling the demand for improved diagnostics and precise therapeutics. Therefore, this review highlights the progress of metabolomics in malaria researches, including metabolic mapping of Plasmodium vertebrate life cycle stages, investigating antimalarials mode of actions and underling complex host-parasite interactions. Also, we discuss current limitations as well as make several practical suggestions for methodological improvements which can drive following metabolomics progress for malaria from a comprehensive perspective.